What God kept for himself : atheism, sodomy, and radical dissent in Renaissance Italy - Grassi, Umberto (I Tatti studies in Italian Renaissance history., 2026)
"Umberto Grassi recovers a radical critique, suppressed by the Inquisition. A wave of 16th-18th century Italians claimed that Adam and Eve had angered God by engaging in sodomy-sexual practice reserved for the divine. The heresy was politically potent, buttressing the common belief that elites invented Christian morality to enforce social control"--